Digital Authenticity under Generative AI: Mechanisms of Synthetic Signal Construction and Strategic Legitimacy in Branding - Nuk Ghurroh Setyoningrum; Ahmad Mundzir (UDEX Institute, 2025)
The diffusion of generative artificial intelligence (GenAI) in branding practices challenges a central assumption in authenticity research: that legitimacy derives primarily from indexical continuity between expressive artifacts and experiential origin. As firms increasingly rely on synthetic systems to produce scalable, adaptive, and stylistically coherent brand communications, the structural linkage between expression and embodied authorship becomes attenuated. This article develops a mechanism-based framework to explain how authenticity and strategic legitimacy are reconstructed under conditions of generative intensification. Integrating signaling theory, legitimacy theory, and dynamic capabilities, the analysis conceptualizes authenticity as an emergent property of orchestrated synthetic signal regimes rather than as an intrinsic attribute of origin. The framework specifies a curvilinear relationship between generative AI intensity and perceived authenticity: moderate integration enhances coherence and responsiveness, while uncalibrated intensification risks signal dilution and perceived artificiality. Perceived authenticity mediates the effect of generative intensity on strategic legitimacy, and synthetic signal orchestration capability conditions the threshold at which legitimacy erosion occurs. Contextual salience, including heritage intensity and customer epistemic sensitivity, further shapes these dynamics. By reframing authenticity as governance-dependent under digital abundance, the article extends branding theory and dynamic capabilities scholarship while providing a structured agenda for empirical examination of AI-enabled marketing transformation.